Factors Contributing to The Relapse of Schizophrenia Patients After Recovery: An Update Narrative Review - Putri, Sriburhani; Sansuwito, Tukimin; Letchmi Panduragan, Santhna (Journal of Health Sciences and Epidemiology, 2024)
Schizophrenia relapse after recovery remains a significant challenge, with multiple factors contributing to its occurrence. Understanding these factors is essential for their effective prevention and management. This narrative review aimed to identify and synthesize the factors contributing to relapse in patients with schizophrenia after recovery. A comprehensive literature search was conducted across PubMed, Scopus, and PsycINFO databases to identify relevant studies. The inclusion criteria were peer-reviewed articles in English, focusing on relapse factors among patients with schizophrenia. Data from the eligible studies were synthesized into thematic domains. A total of fifteen studies spanning diverse populations and designs were included. The key contributing factors identified were as follows: 1) Biological: Medication non-adherence, substance use, and neurobiological predispositions. 2) Psychological: High-stress levels, inadequate coping mechanisms, and comorbid mental health conditions. Limited social support, stigma, and dysfunctional family dynamics. 3) Environmental: Socioeconomic challenges and barriers to healthcare access. Trends have indicated gaps in understanding the interactions among these factors and the lack of culturally tailored interventions. These findings highlight the multifactorial nature of schizophrenia relapse, emphasizing the need for integrated, multidisciplinary approaches to prevention and intervention. Holistically addressing individual, familial, and systemic factors is crucial for reducing relapse rates. This review underscores the importance of tailored, patient-centered interventions and systemic policy changes to address the complex contributors to schizophrenia relapse, thereby improving patient outcomes.